Analisis dan Perencanaan Persediaan Kritis pada Usaha Ritel Penjualan Barang Dagang Kebutuhan Pokok - Febrina, Helda; Abdulrahim, Muslimin (Jurnal Ilmiah Wahana Pendidikan, 2024)
Inventory control is useful for preventing the risk of shortages or excess inventory which could result in store or retail losses. The large number of types and variations of goods sold by retailers makes it difficult to monitor the amount of inventory in the warehouse. This research was carried out using 18 types of goods in the form of the staple commodity rice which has a critical supply value at the XYZ Agent Store. The results of the classification of 18 types of goods are class A with 5 types of goods, which have a total percentage of fund absorption of 77.07%, class B with 5 types of goods which have a total percentage of fund absorption of 17.3%, and class C with 8 types goods that have a total fund absorption percentage of 5.63%. There are also obtained the results of the Inventory Turnover Ratio (ITR), the amount of Safety Stock (SS) and the Reorder Point (ROP).